Thymic Function as a Predictor of Immune Recovery in Chronically HIV-Infected Patients Initiating Antiretroviral Therapy - Rb-Silva, Rita; Nobrega, Claudia; Azevedo, Cecilia; Athayde, Emilia; Canto-Gomes, João; Ferreira, Ivo; Cheynier, Rémi; Yates, Andrew J.; Horta, Ana; Correia-Neves, Margarida (Frontiers in Immunology, 2019)
Poor immunological responders (PIR) are HIV-infected patients with virologic suppression upon antiretroviral therapy (ART) but persistently low CD4+ T cell counts. Early identification of PIR is important given their higher morbimortality compared to adequate immune responders (AIR). In this study, 33 patients severely lymphopenic at ART onset, were followed for at least 36 months, and classified as PIR or AIR using cluster analysis grounded on their CD4+ T cell count trajectories. Based on a variety of immunological parameters, we built predictive models of PIR/AIR outcome using logistic regression. All PIR had CD4+ T cell counts consistently below 500 cells/µL, while all AIR reached this threshold. AIR showed higher percentage of recent thymic emigrants among CD4+ T cells; higher numbers of sjTRECs and greater sj/βTREC ratios; and significant increases in thymic volume from baseline to 12 months of ART. We identified mathematical models that correctly predicted PIR/AIR outcome after 36 months of therapy in 77-87 % of cases, based on observations made until 2-6 months after ART onset. This study highlights the importance of thymic activity in the immune recovery of severely lymphopenic patients, and may help to select the patients that will benefit from closer follow-up or novel therapeutic approaches.